2009
DOI: 10.1007/s11240-009-9611-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type of explant and age, plant growth regulators and medium strength on somatic embryogenesis and plant regeneration in Eucalyptus camaldulensis

Abstract: Plant regeneration was achieved through direct and indirect somatic embryogenesis in Eucalyptus camaldulensis. Callus was induced from mature zygotic embryos and from cotyledon explants collected from 10, 15, 25, and 30-day-old seedlings cultured on Murashige and Skoog (MS) basal medium supplemented with different concentrations of naphthaleneacetic acid (NAA). Maximum callus induction from mature zygotic embryos was obtained on MS basal medium containing 1 mg l -1 NAA. The frequency of callus development vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 34 publications
3
50
1
1
Order By: Relevance
“…Several factors are critical for the induction of embryogenic calli including type and age of explants, culture medium, concentration and combination of plant growth regulators (Prakash and Gurumurthi 2010). In the present study, the size and age of the axillary bud explants were found to be critical for calli induction in D. rotundata.…”
Section: Effect Of Different Concentrations Of Picloram Supplemented mentioning
confidence: 47%
“…Several factors are critical for the induction of embryogenic calli including type and age of explants, culture medium, concentration and combination of plant growth regulators (Prakash and Gurumurthi 2010). In the present study, the size and age of the axillary bud explants were found to be critical for calli induction in D. rotundata.…”
Section: Effect Of Different Concentrations Of Picloram Supplemented mentioning
confidence: 47%
“…NAA at concentrations between 10.8 and 81.0 µM has been used for somatic embryogenesis from C. citriodora, E. camaldulensis, E. dunnii, and E. globulus zygotic embryos, cotyledons, or germinating seedlings, sometimes with the addition of 100 mL L −1 coconut water or 0.5-1 g L −1 casein hydrolysate [73][74][75][76]81,[132][133][134]. NAA at 5.4 µM has been used in combination with 2.22 µM BA or 4.52 µM 2,4-D for inducing embryogenic callus from zygotic embryos, hypocotyls, or cotyledons of E. globulus and E. nitens [134,135], with coconut water at 100 mL L −1 incorporated into the callogenesis medium for E. nitens [135].…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…NAA at 5.4 µM has been used in combination with 2.22 µM BA or 4.52 µM 2,4-D for inducing embryogenic callus from zygotic embryos, hypocotyls, or cotyledons of E. globulus and E. nitens [134,135], with coconut water at 100 mL L −1 incorporated into the callogenesis medium for E. nitens [135]. Callogenesis has been induced using 100 µM indole-3-butyric acid (IBA) for E. globulus hypocotyls or cotyledons [136], while 2.22 µM BA has been used for callogenesis from E. camaldulensis hypocotyls [133]. Picloram at 20.7-50.0 µM induces somatic embryogenesis from E. grandis cotyledons, E. globulus hypocotyls and cotyledons, and E. globulus and E. saligna × E. maidenii F.Muell.…”
Section: Somatic Embryogenesismentioning
confidence: 99%
See 2 more Smart Citations